Conserved chromatin regulators control the transcriptional immune response to intracellular pathogens in Caenorhabditis elegans. - Eillen Tecle; Paaramitha Warushavithana; Samuel Li; Michael J Blanchard; Crystal B Chhan; Theresa Bui; Ryan S Underwood; Malina A Bakowski; Emily R Troemel; Vladimir Lažetić (PLoS Genetics)
Robust transcriptional responses are critical for defense against infection. However, unrestrained immune responses can cause negative impacts such as damaging inflammation and slowed development. Here, we find that a class of transcriptional regulators previously associated with regulation of development in Caenorhabditis elegans, is also involved in repressing immune responses. Specifically, through forward genetics, we find that loss of lin-15B leads to constitutive expression of Intracellular Pathogen Response (IPR) genes. lin-15B encodes a transcriptional repressor with a conserved THAP domain that is associated with the DRM chromatin remodeling complex that regulates C. elegans development. We show that lin-15B mutants have increased resistance to natural intracellular pathogens, and the induction of IPR genes in lin-15B mutants relies on the MES-4 histone methyltransferase. We extend our analyses to other DRM and NuRD chromatin remodeling factors, as well as SUMOylation histone modifiers, showing that a broad range of chromatin-related factors can repress IPR gene expression. Altogether these findings suggest that conserved chromatin regulators may facilitate development in part by repressing damaging immune responses against intracellular pathogens.